Preparation method and application of hard and wear-resistant zinc sulfide anti-reflection protective film
By using a high-temperature substrate, specific deposition rate and AC high-voltage electric field in the preparation process of zinc sulfide film, combined with high-temperature annealing treatment, the problem of insufficient hardness and wear resistance of ZnS film is solved, and efficient wear resistance in the infrared band is achieved performance.
Patent Information
- Application Number
- CN202411349581.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The prior art is difficult to improve the hardness and wear resistance of zinc sulfide (ZnS) films, especially in applications in infrared bands, resulting in their susceptibility to abrasion in windy and sandy weather.
By using a high-temperature substrate and a specific deposition rate during film preparation, and introducing an AC high-voltage electric field into the vacuum chamber, the kinetic energy of the evaporated particles is increased; after preparation, high-temperature annealing is carried out to improve the density of the film and reduce stress.
It significantly improves the hardness and wear resistance of the ZnS film, so that it can be used for a long time in windy and sandy weather without being easily abrasive, meeting the actual needs of infrared monitoring instruments.
Smart Images

Figure CN119220929A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a hard and wear-resistant zinc sulfide anti-reflection protective film, which is used for infrared photoelectric monitoring or monitoring instruments and belongs to the field of optical films. Background Art
[0002] The mid-infrared band with a wavelength of 3 to 5 μm and the far-infrared band with a wavelength of 8 to 12 μm are two important infrared atmospheric windows, which have extremely important application value in the monitoring and supervision of sea and land.
[0003] Since the refractive index of the germanium (Ge) substrate and the zinc sulfide (ZnS) film is well matched, it is widely used in the photoelectric monitoring or monitoring instruments of the above two infrared bands. Because of this, many research results have been reported successively, including the anti-reflection effect, the film structure under different processes, and the moisture resistance, chemical properties and mechanical properties of the film layer, etc., but there are few preparation process studies on how to improve the hardness and wear resistance of the ZnS film. ZnS film is widely used in the infrared band as a low refractive index material, and can also be used as a high refractive index material. It is a typical soft film material, so the hardness and wear resistance of its film layer have always been the focus of people's attention. Yu Juxian of the Kunming Institute of Physics once disclosed a high-strength anti-reflection film (CN 87102489A) of a single-layer zinc sulfide on a germanium substrate. The strengthening process of heat treatment at a specific temperature after the ZnS film prepared by conventional process under cold substrate is greatly improved, and important progress has been made. Summary of the invention
[0004] The invention provides a preparation method and application of a hard and wear-resistant zinc sulfide antireflection protective film.
[0005] A hard and wear-resistant zinc sulfide anti-reflection protective film is required for a far-infrared sea surface monitoring instrument with a wavelength of 8 to 12 μm. The Ge substrate and ZnS film located on the outermost side of the instrument lens need to withstand long-term sand and dust abrasion in the windy and sandy weather in northern my country (such as the Bohai Bay). To this end, the present invention particularly proposes a preparation technology and process factors for enhancing the hardness and wear resistance of the ZnS film. During and after the preparation, a combination of multiple technologies and process factors is adopted. Through the superposition and joint action of multiple measures, the purpose of enhancing the hardness and wear resistance of the ZnS film is effectively achieved to meet the actual use requirements. Obviously, the ZnS film on the Ge substrate has two functions: it is both an anti-reflection film for Ge and an anti-wear protective film.
[0006] A hard and wear-resistant zinc sulfide antireflection protective film, which is composed of a germanium (Ge) substrate and a zinc sulfide (ZnS) film. The only way to obtain a hard and wear-resistant ZnS film is to increase the kinetic energy of the evaporated particles during deposition: E = 3kT / 2, where E is the kinetic energy of the evaporated particles during deposition, and k is the Boltzmann constant (=8.62x10 -5 eV / °K), T is the Kelvin temperature when the thin film material evaporates. It is known that the temperature of ZnS material when it evaporates is 1373°K, so its kinetic energy E is only 0.18eV. Obviously, this kinetic energy is too low, so the ZnS film prepared by conventional technology cannot be hard and wear-resistant.
[0007] To this end, the present invention proposes the following three concepts: When preparing the thin film, the Ge substrate needs to maintain a specific high temperature. To achieve this goal, the ZnS film needs to select a specific evaporation method and maintain a specific deposition rate, which can be an important first step for the ZnS film to grow a hard and wear-resistant film on a high-temperature substrate. The second step requires the introduction of a new AC high-voltage electric field in the vacuum chamber of a commercial coating machine to further increase the kinetic energy of the ZnS evaporated particles in the process of traveling from the evaporation source to the substrate, thereby enhancing the hardness and wear resistance of the ZnS film. The third step is to implement a high-temperature annealing treatment in the air after the film is prepared to further improve the film density and reduce the film layer stress. The following is a detailed explanation.
[0008] 1. Use a specific high temperature substrate and deposition rate
[0009] It is well known that the hardness or wear resistance of a thin film strongly depends on the substrate temperature during film deposition, because a high-temperature substrate can significantly increase the energy of the deposited molecules and increase the mobility of the deposited molecules on the substrate surface, causing the film layer to grow in a preferential orientation and form a dense, hard, and wear-resistant thin film structure.
[0010] The substrate temperature during deposition is particularly sensitive to the growth of ZnS thin film. The ZnS film deposited on a cold substrate (room temperature) is very soft and has very poor firmness, so the present invention proposes that high-temperature substrate deposition must be used. Unfortunately, as the substrate temperature increases, the reverse evaporation of the ZnS film (i.e., the film molecules deposited on the substrate will evaporate and leave the substrate) will cause deposition to become very difficult, or even completely unable to form a film. This is what people often say "ZnS film cannot be deposited on a high-temperature substrate", which is also the reason why ZnS films in the prior art are often deposited on a cold substrate or a low-temperature substrate. Pulker also pointed out in his early years that when the substrate temperature reaches 300°C, the ZnS film at a conventional deposition rate will completely stop depositing.
[0011] By the way, what is a high-temperature substrate? Usually, room temperature refers to a cold substrate, that is, the substrate is not heated during film deposition; low-temperature substrate deposition refers to the situation where the substrate temperature is heated to below 150°C, while high-temperature substrate deposition refers to the situation where the substrate temperature is heated to above 150°C. For high-temperature substrate deposition, it has been experimentally confirmed that when the substrate temperature is above 250°C, not only is the reverse evaporation serious and deposition difficult, but the structure of the ZnS film becomes coarser and the scattering increases. Therefore, the so-called high-temperature substrate deposition of ZnS film actually refers to the situation of 150-250°C.
[0012] So, how to overcome the bottleneck of ZnS film deposition on high-temperature substrates? To this end, the present invention first studies the relationship between the deposition rate of ZnS film and its substrate temperature, proposes the concept of deposition coefficient, and expresses the deposition coefficient ɑ as:
[0013]
[0014] Where N + and N - They represent the number of ZnS atoms or molecules evaporated to the substrate and de-evaporated, i.e., desorbed from the substrate. C is dependent on N + A quantity, N + The larger is, the smaller is C, and the larger is ɑ. U represents the adsorption energy, k is the Boltzmann constant, and T is the substrate temperature. Obviously, and The relationship between is a straight line within a certain range, and the slope of the straight line is This shows that the deposition coefficient ɑ of the film depends not only on the substrate temperature, but also on the deposition rate of the film. In order to study the relationship between the deposition coefficient of the ZnS film and the substrate temperature and deposition rate, the present invention conducted an experimental study and obtained the following results for two specific deposition rates of 0.97nm / s and 9.5nm / s: Figure 2 The relationship between the deposition coefficient ɑ and the substrate temperature T of the ZnS film is shown in FIG. Figure 2 It can be seen that at the same substrate temperature, different deposition rates give completely different deposition coefficients. For the sake of intuitiveness, the present invention lists the experimental results in Table 1. As can be seen from Table 1, at a substrate temperature of 200°C, if a conventional deposition rate of 0.97nm / s is used, the deposition coefficient is only 0.33. At this time, not only is the ZnS film difficult to deposit, but a large amount of ZnS evaporation material is wasted. However, if the ZnS deposition rate is increased from 0.97nm / s to 9.5nm / s, the deposition coefficient can be increased to 0.68. That is to say, on a high-temperature substrate, the bottleneck of the difficulty in depositing ZnS film can be significantly alleviated by increasing the deposition rate. This is a new method for depositing ZnS film on a high-temperature substrate proposed by the present invention, which makes it possible to deposit ZnS film on a high-temperature substrate.
[0015] Table 1
[0016]
[0017] Figure 2 The relationship between the deposition coefficient ɑ and the substrate temperature T shown in the figure is tested by the following method: Figure 1 The quartz crystal control piece 12 controls the film thickness, and the crystal control piece is water-cooled to keep it at room temperature. Then the coating substrate 5 (5') on the workpiece holder 4 is heated to 100℃, 150℃, 200℃, and 250℃ respectively, and the same thickness of ZnS film is evaporated on the thickness control piece at the same deposition rate of 0.97nm / s. Finally, the thickness of the ZnS film on the substrates at various temperatures is measured by photometry or other thickness gauges, and the ratio of the thickness on the substrates at the above temperatures to the thickness at room temperature is measured to obtain the deposition coefficient ɑ, thus obtaining Figure 2 The same method is used to test the deposition rate of 9.5nm / s, and we get Figure 2 Curve 2.
[0018] It should be noted that the deposition rate of ZnS is 0.97nm / s and 9.5nm / s. In the visible light region, the central wavelength λ 0 =550nm, the refractive index of ZnS film is 2.35, for a λ 0 / 4 optical thickness, its geometric thickness is 59nm, the evaporation time using conventional technology is about 1 minute, that is, the deposition rate is about 1nm / s, while the actual experiment is controlled at 0.97nm / s. 0 =10μm, the refractive index of the ZnS film is 2.2, and similarly for a λ 0 / 4 optical thickness, its geometric thickness is 1136nm, the evaporation time using conventional process is 19 minutes, the present invention shortens the evaporation time to about 2 minutes to increase the deposition rate, that is, the deposition rate is about 10nm / s, while the actual experiment is controlled at 9.5nm / s.
[0019] It should also be pointed out that although the prior art often uses crucible heating to evaporate ZnS materials, the present invention must use electron beam heating evaporation technology in order to achieve a deposition rate 10 times higher than the prior art on a high-temperature substrate. The present invention found that there are several disadvantages of using crucible heating evaporation: first, the evaporation rate is very slow, and it cannot reach the deposition rate of about 10nm / s required by the present invention; second, the generated ZnS film is a mixture of sphalerite and wurtzite. This ZnS film is easily converted into ZnO when exposed to ultraviolet rays for a long time during use, and the film layer is relatively soft, while the ZnS film generated by electron beam evaporation is a stable sphalerite cubic structure, and the film layer is relatively hard; and when ZnS is evaporated in a crucible, the material decomposes severely, and a lot of decomposed black zinc will remain at the bottom of the crucible, especially when the evaporation rate is faster, resulting in a greatly increased absorption of the ZnS film. This shows that electron beam heating evaporation technology must be used when evaporating ZnS film on a high-temperature substrate.
[0020] 2. Introducing AC high voltage electric field
[0021] ZnS is a very unique thin film material. It completely sublimates and produces ionization during vacuum evaporation: Zn + and S - During the film deposition process, Zn + and S - It will recombine on the substrate, so a film with the same stoichiometry as ZnS can still be obtained. This mechanism of film deposition in elemental state can well explain the phenomenon that the deposition coefficient of ZnS film decreases rapidly as the substrate temperature rises.
[0022] Based on the ionization generated when ZnS material evaporates, the present invention assumes that if an AC high voltage electric field is installed in the vacuum chamber of a commercial coating machine, the ion Zn + and S - In the process of traveling from the evaporation source to the substrate, the ions are inevitably affected by a strong electric field, which will greatly increase the kinetic energy of the ions and improve the hardness and wear resistance of the film.
[0023] So how to introduce an AC high voltage electric field into the vacuum chamber? The introduced AC high voltage electric field cannot affect the original functions of the commercial coating machine. To this end, the present invention conceives the following configuration scheme: Figure 1As shown, between the electron beam evaporation source 10 in the vacuum chamber and the substrate workpiece rack 4, a pair of electrodes 7, 7' are arranged close to the workpiece rack. The electrodes 7, 7' are composed of two semicircular rings made of pure aluminum plates. The distance between them and the workpiece rack varies depending on the size of the vacuum chamber, generally 20 to 100 mm, and the preferred distance in the present invention is 50 mm. The width (i.e., height) of the two semicircular ring electrodes is 10 to 40 mm, and the preferred height in the present invention is 20 mm. When evaporating ZnS material under high vacuum conditions, an AC high voltage with a frequency of 50 Hz and a voltage of 3.2 to 3.6 KV is applied to the electrodes 7, 7', and the preferred voltage in the present invention is 3.4 KV. Because the high-voltage electric field will not produce any glow discharge under high vacuum conditions, the current is zero. The two pure aluminum semicircular ring electrodes 7, 7' are supported by stainless steel high-voltage introduction electrodes 8, 8', connected to the high-voltage transformer 16, and insulated from the high voltage of the coating machine.
[0024] The diameter of the ring formed by the two semicircular rings is similar to the diameter of the workpiece frame, generally 200 to 1200 mm, and the preferred diameter of the present invention is 400 mm (see Figure 3 ), that is, the radius of the two semicircular rings is preferably 200 mm. The two semicircular rings are cut from pure aluminum plates with a thickness of about 1.2 mm. Because the two semicircular rings need to be insulated from each other, they are separated by 40 mm. At the same time, the two semicircular rings are wrapped with clean pure aluminum foil with a thickness of 0.01 mm, and the aluminum foil is replaced after each ZnS film preparation to reduce the contamination of the ZnS film by the coating material deposited on the electrode.
[0025] Experiments have proved that the above idea is feasible and the conception is correct.
[0026] 3. Implement high temperature annealing treatment
[0027] After the ZnS film is prepared, it needs to be subjected to high-temperature annealing treatment in the air. This method is simple and easy to implement, so the existing technology adopts this method, but the process parameters of the treatment vary with different equipment and the shape and size of the sample. The so-called process parameters mainly include: the first is the average temperature at constant temperature; the second is time, including heating time, constant temperature time, cooling time, and the time for the sample to be taken out of the vacuum chamber and into the oven; the third is the atmosphere, which is commonly air, and nitrogen can also be used; the fourth is the placement method of the ZnS film sample, including flat placement, vertical placement, etc.; the fifth is the material and shape of the sample placement tool, etc. After the ZnS film is prepared, it is subjected to high-temperature annealing treatment, which can not only change the microstructure of the ZnS film layer and make the film layer denser, but also reduce the stress of the film, especially the zinc sulfide film of the present invention, whose working band is 8μm~12μm, and the corresponding film thickness is very thick, and the compressive stress is very large, so the annealing process is very important. In terms of high-temperature annealing treatment, the present invention mainly optimizes the process parameters and designs a special sample tool (see Figure 4 ).
[0028] The above three measures are important for preparing hard and wear-resistant zinc sulfide antireflection protective film. Only when multiple technologies and process measures are used in an overlapping and synergistic manner can the hardness and wear resistance of the ZnS film be effectively improved to meet the actual use requirements.
[0029] To achieve the above purpose, the specific technical solution adopted by the present invention is:
[0030] A hard and wear-resistant zinc sulfide antireflection protective film consists of a substrate and a film, wherein the substrate is germanium and the film is zinc sulfide.
[0031] A method for preparing a hard and wear-resistant zinc sulfide antireflection protective film comprises the following steps:
[0032] S1: When preparing ZnS thin film, the substrate needs to maintain a high substrate temperature and select a specific evaporation method to maintain a high deposition rate for thin film deposition. At the same time, an AC high voltage electric field is set in the vacuum chamber to increase the kinetic energy of the deposited particles on the substrate.
[0033] Furthermore, when preparing the thin film, a germanium substrate is used, and an AC high voltage electric field of 3000V to 3800V is set in a vacuum chamber. The evaporation method of the zinc sulfide anti-reflection protective film uses an electron beam evaporation source to evaporate zinc sulfide, maintaining a deposition rate of 6nm / s to 15nm / s;
[0034] S2: After the zinc sulfide anti-reflection protection is prepared, annealing treatment is performed in air to obtain a hard and wear-resistant zinc sulfide anti-reflection protection film on the germanium substrate.
[0035] Furthermore, the substrate temperature is set to 200° C. to 240° C., and the constant temperature time is 1 to 3 hours.
[0036] Furthermore, the thin film evaporation method uses electron beam evaporation technology.
[0037] Furthermore, the film deposition rate is 8 nm / s to 12 nm / s.
[0038] Furthermore, the voltage of the AC high voltage electric field is 3200V to 3600V, the current is zero, and the frequency is 50Hz.
[0039] Furthermore, the high temperature annealing treatment temperature in air is 330° C. to 370° C., and the constant temperature time is 4 to 8 hours.
[0040] Furthermore, the temperature of the high-temperature substrate is 215° C. to 225° C. The substrate temperature is most preferably 220° C., and the constant temperature time is 2 hours.
[0041] Furthermore, electron beam evaporation technology is used to maintain a deposition rate of 9 nm / s to 11 nm / s. Most preferably, the film deposition rate reaches about 10 nm / s.
[0042] Furthermore, the voltage of the AC high-voltage electric field is 3300V to 3500V, and the voltage of the AC high-voltage electric field is most preferably 3400V.
[0043] Furthermore, the annealing conditions are: high temperature annealing at 345°C to 355°C for 5 to 7 hours. The most preferred annealing temperature of the film in air is 350°C, and the constant temperature time is 6 hours.
[0044] Finally, the working wavelength band of the zinc sulfide film on the germanium substrate is 8 μm to 12 μm. The refractive index of the germanium substrate in the working wavelength band is 4.0, the refractive index of the zinc sulfide film in the working wavelength band is 2.2, and its geometric thickness is 1136 nm.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] In view of the specificity of ZnS materials, the existing technology often uses cold substrate to deposit ZnS film, avoiding the bottleneck problem of difficult deposition on high temperature substrate. + and S - The ion energy is too low, and the mobility of the deposited molecules or atoms is almost zero after reaching the substrate surface, so the generated ZnS film is very soft. At this time, even if it is subjected to high-temperature annealing in air after preparation, the hardness and wear resistance of the final ZnS film still cannot meet the use requirements.
[0047] To obtain a hard and wear-resistant ZnS film, the measures taken during film preparation are far more important than the post-preparation treatment. To this end, the present invention uses a high-temperature substrate and introduces an AC high-voltage electric field during film preparation to greatly improve the deposition of ZnS. + and S - The energy of the ions. In this way, the deposited particles with sufficient energy collide with the surface of the deposited film, generating a sufficiently large momentum transfer, the deposited particles obtain a sufficiently large mobility, the film produces sufficient preferential growth, and its diffraction spectrum shows a sharp and strong (111) diffraction peak near the diffraction angle of 28°. This film has sufficient hardness and wear resistance. Since the ZnS film of the present invention has formed sufficient hardness and wear resistance during the deposition process, it is further subjected to high-temperature annealing treatment in the air to achieve the purpose of icing on the cake, and obtain hardness and wear resistance that can fully meet practical requirements and withstand long-term abrasion by sand and dust. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a schematic diagram of the configuration of the vacuum evaporation system of a commercial coating machine and the AC high voltage electrode of the present invention.
[0049] Figure 2 It is the relationship curve between the deposition coefficient of the ZnS film of the present invention and the substrate temperature at different deposition rates.
[0050] Figure 3 It is a schematic diagram of an electrode pair composed of two semicircular pure aluminum rings in the present invention.
[0051] Figure 4 This is a sample annealing processing tooling diagram used in the present invention.
[0052] Figure 5 It is a spectral transmittance curve of a hard and wear-resistant ZnS anti-reflection protective film of the present invention. DETAILED DESCRIPTION
[0053] Before proposing the concept of the present invention, it is necessary to explain the vacuum evaporation system of the commercial coating machine. Figure 1 As shown, it mainly includes a vacuum chamber 1, and high vacuum is obtained by exhausting the air through the exhaust port 2. In the vacuum chamber, a coating substrate heating system 3 is provided to heat the substrate to a specific temperature before coating. Immediately below the heating system 3 is a workpiece rack 4 for placing the coating substrate. The workpiece rack is a disc that can carry many coating substrates (such as 5, 5'). During coating, the workpiece rack rotates evenly and quickly. A film thickness monitoring film box 6 (i.e., monitoring film) is set at the center of the disc. The thin film material evaporation source is composed of a crucible heating evaporation source 9 and an electron beam heating evaporation source 10. The two evaporation sources can be selected according to different evaporation materials. There is a baffle 11, 11' above the evaporation source to control the vapor of the evaporation material so as to accurately control the thickness of each layer of the film. The film thickness monitoring system can use a quartz crystal control film 12, or a light control system can be selected. The light control system is composed of a light source 13, a filter 14, a monitoring film and a photoelectric receiver 15.
[0054] use Figure 1 The commercial vacuum coating machine vacuum evaporation system and the AC high voltage electrode installed in the present invention are used to deposit zinc sulfide film on a germanium substrate, and the working band is 8μm to 12μm. The refractive index of the germanium substrate in the working band is 4.0, the refractive index of the zinc sulfide film in the working band is 2.2, and the central wavelength λ 0 =10μm, the optical thickness of the zinc sulfide film is λ 0 / 4, the corresponding geometric thickness is 1136nm.
[0055] The additional AC high voltage electrodes 7, 7' are located between the thin film material evaporation sources 9, 10 and the Ge substrate workpiece holder 4. Figure 1As shown. The electrodes 7, 7' are composed of two semicircular rings made of pure aluminum plates. The distance between them and the workpiece holder 4 varies depending on the size of the vacuum chamber, and is generally 20 to 100 mm. The preferred value in the present invention is 40 mm. The width (i.e., height) of the two semicircular ring electrodes is 10 to 40 mm. The preferred value in the present invention is 20 mm. When evaporating ZnS material under high vacuum conditions, an AC high voltage with a frequency of 50 Hz and a voltage of 3.2 to 3.6 KV is applied to the electrodes 7, 7'. The preferred voltage in the present invention is 3.4 KV. The two pure aluminum semicircular ring electrodes 7, 7' are supported by stainless steel high-voltage lead-in electrodes 8, 8' and are connected to a high-voltage transformer 16. Figure 3 It is a schematic diagram of an electrode pair composed of two semicircular pure aluminum rings of the present invention. The separation of the two semicircular rings is about 40mm to effectively prevent sparks under high vacuum conditions. The size of the ring varies depending on the size of the workpiece holder 4. Generally, the diameter of the ring is approximately the same as the diameter of the workpiece holder, such as 200-1200mm, and the preferred diameter of the present invention is 400mm. Electrodes 7, 7' are directly cut from pure aluminum plates with a thickness of 0.5-2mm, and the preferred thickness of the present invention is 1.2mm. The steps for making the electrode are: 1. Cut two electrode plates from a pure aluminum plate with a thickness of 1.2mm according to a semicircular circumference πR equal to 628mm and a width of 20mm; 2. Bend the above two electrode plates into two semicircular rings at R=200mm, and assemble them into a circle; 3. In order to prevent the two semicircular rings from sparking each other, cut off 20mm at each contact position, and finally form a circle. Figure 3 looks like.
[0056] Before preparing the ZnS film, the germanium substrate is gradually heated to 220°C. After being kept warm for 2 hours, the ZnS crystalline block material is heated and evaporated by an electron beam. At the same time, an AC voltage of 3.4KV is applied to the high-voltage electrodes 7 and 7'.
[0057] Depend on Figure 2 It can be seen that when the substrate temperature is 220℃, if the conventional deposition rate of about 1nm / s is used for evaporation, the deposition coefficient of the ZnS film is only 0.22, that is, 78% of the deposited molecules are re-evaporated, which not only causes a large amount of ZnS material loss, but also the film thickness increases very slowly. The final result is that all the ZnS material added by the electron beam evaporation source is evaporated, but the film thickness is still less than λ 0 / 4. To this end, a high deposition rate of about 10nm / s must be selected for evaporation. Figure 2 It can be seen that the deposition coefficient of the ZnS film can reach 0.6, thus successfully completing the optical thickness λ 0 / 4, that is, a ZnS film with a geometric thickness of 1136nm is deposited.
[0058] After completing the ZnS film deposition, turn off the substrate heating system and the 3.4KV AC high voltage, cool the coated sample, and when the sample temperature is lower than 60°C, take out the coated sample from the vacuum chamber and transfer it into a baking furnace for high-temperature annealing in the air. The annealing temperature is 330°C to 370°C, and the preferred temperature in the present invention is 350°C; the annealing constant temperature time is 4 to 8 hours, and the preferred temperature in the present invention is 6 hours. During annealing, the oven needs to heat up slowly for about 2 hours, then keep the temperature constant for 6 hours, and finally cool down slowly for more than 12 hours. Due to the different models and specifications of the ovens, the heating and cooling times vary greatly, but generally ovens have the problem of heating up and cooling too quickly. To this end, the present invention is designed Figure 4 The sample fixture shown is made of stainless steel. Since the thermal conductivity of stainless steel is low, only about 20W / (mk), this fixture can both increase the heat capacity and delay the heating and cooling time, thus overcoming the problems of too fast heating and cooling time and too large temperature fluctuations during constant temperature. Figure 4 In the figure, 1 is a stainless steel tool, 2 is an aluminum foil, and 3 is an annealed sample. The ZnS film is placed flat on an aluminum foil with a thickness of 0.05 mm with the ZnS film facing upward. During annealing, another tool with the same concave hole as 1 is used to cover the ZnS film downward. Figure 4 1 above.
[0059] Finally, the ZnS anti-reflection protective film was tested for its spectral properties, hardness and wear resistance. Figure 5 The solid line shown is the spectral transmittance curve of the sample after being coated with ZnS film, and the dotted line is the transmittance curve of a single Ge surface without ZnS film. It can be seen that the ZnS film has an excellent wide-spectrum transmittance enhancement effect on the Ge surface. In terms of the film hardness and wear resistance test, the present invention mainly adopts a simple and easy relative comparison method, using pencils of different hardness to repeatedly scratch the film surface back and forth. Currently, 1H to 10H hard core pencils can be bought on the market. The larger the number in front, the higher the hardness. The ZnS film of general technology can generally only withstand repeated scratches with 1H to 2H pencils at most, while the present invention uses 9H or 10H pencils to repeatedly scratch without any scratches.
Claims
1. A method for preparing a hard and wear-resistant zinc sulfide antireflection protective film, characterized in that: The following steps are involved: S1: When preparing the film, a germanium substrate is used, and an AC high voltage electric field of 3000V to 3800V is set in a vacuum chamber. The evaporation method of the zinc sulfide antireflection protective film uses an electron beam evaporation source to evaporate zinc sulfide, maintaining a deposition rate of 6nm / s to 15nm / s; S2: After the zinc sulfide anti-reflection protection is prepared, annealing treatment is performed in air to obtain a hard and wear-resistant zinc sulfide anti-reflection protection film on the germanium substrate.
2. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 1, characterized in that: In step S1, a high temperature substrate is used as the germanium substrate, and the temperature of the high temperature substrate is 200°C to 240°C.
3. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 2, characterized in that: In step S1 , the temperature of the high temperature substrate is 215° C. to 225° C.
4. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 2, characterized in that: In step S1, the high temperature substrate is heated for 1 to 3 hours.
5. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 1, characterized in that: In step S1, the voltage of the AC high voltage electric field is 3200V to 3600V.
6. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 5, characterized in that: In step S1, the voltage of the AC high voltage electric field is 3300V to 3500V.
7. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 1, characterized in that: In step S1, the deposition rate is maintained at 8 nm / s to 12 nm / s.
8. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 7, characterized in that: In step S1, the deposition rate is maintained at 9 nm / s to 11 nm / s.
9. The method for preparing a hard and wear-resistant zinc sulfide antireflection protective film according to claim 1, characterized in that: In step S2, the annealing conditions are: high temperature annealing at 330°C to 370°C for 4 to 8 hours.
10. An infrared monitoring instrument, characterized in that: A hard and wear-resistant zinc sulfide antireflection protective film prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Low-temperature preparation method for thin film optical filters
CN109355629A
Medium-wave infrared anti-reflection film suitable for wide-angle incidence and preparation method of medium-wave infrared anti-reflection film
CN117761806A
Vacuum coating machine
CN209260185U
Optical film of monolayer ZnS for Germanium substrate
CN87102489A
